Students’ Behavior and Vocabulary Achievement: The Correlation in Learning English - Agusma, Inda (English Education Department, 2025)
This study aims to find out the students’ behavior in learning discipline towards vocabulary achievement and the correlation of these in eleventh grade students at SMA Negeri 1 Kelapa. The research method used is quantitative with correlational design. The data were collected from questionnaire on students’ behavior and test of vocabulary. The data collection technique was carried out using questionnaire on students’ behavior towards learning which was already validity at school. A total of 20 statement items were declared valid and declared reliable, because the results of rcount > rtable were 0,749 > 0,361. The test using vocabulary test of eleventh grade in students in Vocabulary achievement. The total of 24 questions of vocabulary test items were declared valid and reliable the result was 0,805 > 0,361.The data were analyzed using Pearson’s Product-Moment Correlation. The results showed that rxy (0.477) was higher that table at 5% significant level (0.320) which considered that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. There was a significant correlation between students’ behavior and students’ English achievement. The students’ behavior and vocabulary achievement showed positive correlation with the majority of level grade showed a strong correlation category.